Accelerating scientists’ knowledge turns - Goble, C; De Roure, D; Bechhofer, S (Springer Berlin Heidelberg, 2012)
A “knowledge turn” is a cycle of a process by a professional, including the learning generated by the experience, deriving more good and leading to advance. The majority of scientific advances in the public domain result from collective efforts that depend on rapid exchange and effective reuse of results. We have powerful computational instruments, such as scientific workflows, coupled with widespread online information dissemination to accelerate knowledge cycles. However, turns between researchers continue to lag. In particular method obfuscation obstructs reproducibility. The exchange of “Re-search Objects” rather than articles proposes a technical solution; however the obstacles are mainly social ones that require the scientific community to rethink its current value systems for scholarship, data, methods and software.